Structural basis for +1 ribosomal frameshifting during EF-G-catalyzed translocation - Gabriel Demo; Howard B. Gamper; Anna B. Loveland; Isao Masuda; Christine E. Carbone; Egor Svidritskiy; Ya-Ming Hou; Andrei A. Korostelev (Nature Communications, 2021)
Translational frameshifting is a mechanism that expands the coding capabilities of mRNA. Here, structures of 70S ribosome complexes with GTPase elongation factor G (EF-G), a +1-frameshifting-prone mRNA and tRNAs reveal the cooperation between the ribosome and EF-G to induce +1 frameshifting during the translocation step.